Small Business Management and Financial Literacy for Young Entrepreneurs - Lila Maria Kaban; Rifin Khong; Efin Shu; Jony, Jony (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Youth entrepreneurship contributes to the social, cultural, and economic development of society, especially in many developing countries. The idea of encouraging young people to start businesses for a variety of reasons is now widely encouraged. However, there are many challenges and doubts faced in starting a business particularly after the Covid-19 is over. Therefore, the community service was carried out by lecturers at Business School, Universitas Pelita Harapan Medan Campus, providing the onsite seminar and training to 70 high school students at Santo Nicholas School in February 2023. The purpose of the community service was to encourage the students to plan their business projects by presenting data and information on the latest trends and issues in entrepreneurship and finance, as well as conducting one-to-one sessions with the students. Most of the students were enthusiastic throughout the activities resulting in several business plans and proposals being created at the end of the community service. It is implied that young people are indeed motivated to begin their entrepreneurship journey and school is the right place for them to acquire the necessary knowledge and skills. Teachers and parents are suggested to continue to assist the students by providing the commitment and funding required to begin and sustain the business.